Critical theory of information in Brazil: Armand Mattelart's contribution - DOI: 10.3395/reciis.v3i3.285en - Carlos Alberto Ávila Araujo (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
In this article we identify some of Armand Mattelart's main ideas which offer possible approaches to issues addressed by information science. Special attention is given those of his ideas which are connected with the ideological analysis of informational materials and exposing inequities in the international flows of communication (connected with the cultural imperialism theory), and his criticism of the notion of "information society". There are aspects in common between these ideas and those from the areas of "social information" and cultural action, in the field of Library and Information Studies and Information Science in Brazil. In conclusion, the author's attitude as a critical thinking intellectual is highlighted. He is permanently opposing the figure of the positivist administrative scientist who focuses exclusively on technical issues and who seeks to resolve all tensions by developing technological apparatuses.